(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Schizophrenia is a major psychotic disorder in the field of psychiatry. One of the important sequelae of chronic schizophrenia is attempted suicide or suicide. The leading cause of death among schizophrenic patients is completed suicide. Place of study: This study was conducted in the outpatient and inpatient of the departments of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, National Institute of Mental Health (NIMH), Sher-E-Bangla Nagar, Dhaka, and Mental Hospital, Pabna from 30th September 2007 to 29th February 2008. Objective: The present study was designed to determine the reasons for suicidal attempt, socio-demographic features and the methods of attempted suicide among the schizophrenic patients with history of suicidal attempt. Method: This is a cross sectional study on one hundred and two schizophrenic patients who had the history of suicidal attempt. Results: All patients were interviewed by using the semi-structured questionnaire which was developed according to study requirement. It contains sociodemographic and other relevant information. Among 102 cases of schizophrenic patients with suicidal attempt, 72.5% were young; mean age was 31.28 years (SD±8.53) and majority were of male gender (75.5%). Most of them were unemployed (36.3%) and unmarried (49.0%). Forty-five patients (44.1%) had positive family history of psychiatric illness. 03 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Mean duration of suffering from schizophrenia was 8.24 years (SD±5.81). Most of the patients (41.2%) attempted suicide in their earlier course of illness (within 5 years). 64.7% patients attempted multiple times. Most frequent reason for the suicidal attempts was depression (82.4%); 79.4% attempted in recovery phase. The methods mostly applied were ingestion of poison/corrosive (28.4%) and hanging (25.5%). Conclusion: This study tried to find out the possible reasons and sociodemographic correlates of attempted suicide in schizophrenic patients. A study in the community level can pin point the causes of suicidal attempts. However this study is an eye opening in this field. It should be remembered that the rate of completed suicide is more in those patients who had attempted suicide earlier. Awareness in the community, caregivers, and health professionals is very important to save the lives of those schizophrenic patients with suicidal attempts/intent. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22894 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014